2020
DOI: 10.3390/ijns6030068
|View full text |Cite
|
Sign up to set email alerts
|

The Success of a Screening Program Is Largely Dependent on Close Collaboration between the Laboratory and the Clinical Follow-Up of the Patients

Abstract: Neonatal screening for congenital adrenal hyperplasia due to 21-hydroxylase deficiency is now performed in an increasing number of countries all over the world. The main goal of the screening is to achieve early diagnosis and treatment in order to prevent neonatal salt-crisis and death. The screening laboratory can also play an important role in increasing the general awareness of the disease and act as the source of information and education for clinicians to facilitate improved initial care, ensure prompt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In the study by El-Maouche et al, the nontraumatic fracture rate was higher in classic than in NC CAH ( 18 ), which resembles our findings. Why patients with the I2 splice genotype did not have an increased fracture rate is unclear, but since many of them were born before the introduction of neonatal screening in Sweden 1986 ( 45 ), some were probably not diagnosed in the neonatal period and could have been exposed to a prolong period of androgen excess. However, although some patients with I172N genotype were probably diagnosed late, they still had increased fracture rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by El-Maouche et al, the nontraumatic fracture rate was higher in classic than in NC CAH ( 18 ), which resembles our findings. Why patients with the I2 splice genotype did not have an increased fracture rate is unclear, but since many of them were born before the introduction of neonatal screening in Sweden 1986 ( 45 ), some were probably not diagnosed in the neonatal period and could have been exposed to a prolong period of androgen excess. However, although some patients with I172N genotype were probably diagnosed late, they still had increased fracture rate.…”
Section: Discussionmentioning
confidence: 99%
“…After the confirmatory testing, it is recommended to perform a follow-up with clinical evaluation and to start the appropriate treatment as indicated by the therapeutic guidelines. The interaction between the laboratory group and the clinical follow-up team is essential for the achievement of better outcomes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported CAH screening would be either unlikely to be cost-effective or cost-effective only if a single test is performed [19,38]. While recent studies in Canada, Brazil and Sweden concluded that NBS screening for CAH enables to reduce morbidity and mortality [39,40] as well as costs associated with adverse outcomes, transportation, and hospitalization length [41]. The long-term health benefits of NBS for CAH are unknown and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%